Partial melting of granodiorite: insights from ediacaran granulite-facies metamorphism in Southern Brazil. (31st March 2021) - Pavan, M; Sawyer, E W; Moraes, R; Faleiros, F M
Abstract: In the Southern Ribeira Belt (Brazil), the Itatins Complex, composed of ortho- and para-derived migmatites record granulite facies metamorphism. Our work focuses on the ortho-derived migmatite, which displays features indicative of partial melting ranging from in-situ melting (cm-thick lenses and veins) to accumulations of melt as leucosomes and patches of diatexite. The unit comprises a biotite felsic granulite (metagranodiorite) with a residual neosome and a leucocratic neosome, generally referred to as leucosome. Phase equilibria modelling using a modified bulk composition from the geochemical standard JG-1 (granodiorite) was carried out to evaluate whether a protolith of granodiorite bulk composition could produce the mineral assemblages observed in the residual neosome and the compositions of melt and residue produced by the partial melting. Isopleth thermobarometry of plagioclase, biotite and orthopyroxene points to P-T conditions of 0.7–1.0 GPa and 845–872 ºC. The modified granodiorite bulk composition generated just 10 mol % melt at these conditions, far lower than the amount estimated from outcrops (around 32 %). A T-XH2O pseudosection shows that increasing H2 O content enhances the fertility of the bulk composition and it can become capable of producing melt volumes similar to that observed in outcrop. The melt compositions determined for partial melting of the modified granodiorite bulk composition in open- and closed-systems using THERMOCALC are granitic, and peraluminous. The melts have SiO2 contents between 52.02 mol % and 77.27 mol. % and show XFe values of 0.68 and 0.86. In K2 O vs. Na2 O+CaO, K2 O vs. XFe and K2 O-(FeO+MgO)-(Na2 O+CaO) space natural samples (5 from the residual neosome and 2 from leucosome) from the Itatins Complex plot in the direction of the trends for melt and residue compositions obtained from modelling of the modified granodiorite bulk composition. The differences between modeled compositions and real rocks are interpreted to result from the interaction of melt with its residual counterpart. Chondrite normalized REE patterns from the residual neosome shows considerably greater depletion of HREE than geochemical standard JG-1 (granodiorite), and the two analyzed leucosomes show lower HREE contents. Zircon rims have REE patterns interpreted to indicate metamorphic recrystallization. U-Pb zircon Concordia ages indicate that the protolith formed during the Paleoproterozoic (2137 Ma) but that metamorphic recrystallization is Neoproterozoic (between 632 and 601 Ma). The metamorphic age pre-dates the intense granitic magmatism that affected the Southern Ribeira Belt between 600 and 570 Ma.